Hygienic complementary feeding practice and its associated factors among mothers having children aged 6–23 months in Antsokia Gemza district, Ethiopia: a cross-sectional survey - Eyob Ketema Bogale; Tefera Chane; Getachew Tadegew (BMJ Public Health)
Objective To assess the magnitude of parental hygienic complementary feeding practices (PHCFPs) and their associated factors among mothers with children aged 6–23 months in Antsokia Gemza district, Ethiopia, in 2022.Methodology A community-based cross-sectional study was conducted in Antsokia Gemza district, North Shoa, Ethiopia, from 25 June to 22 July 2022. A systematic random sampling technique was applied to select study participants. A total of 391 respondents participated in the study. All mothers (biological mothers, grandmothers, sisters and others) taking responsibility for caring for a child of age 6–23 months were included in the study. Data were collected by using interviewer-administrated questionnaires. Data were entered into Epi-Data V.3.1 and exported to SPSS V.25 for data cleaning and further analysis. Bivariable and multivariable binary logistic regression were employed to identify predictor variables of hygienic practice in complementary feeding with a p value <0.25 entered into the multivariable logistic regression model. Independent variables with a 95% CI and p values <0.05 in multivariable logistic regression were considered statistically significant.Result The magnitude of good parental hygienic practice during complementary feeding of their children aged 6–23 months was 45.3%, with a 95% CI (40.2%–50%). Maternal age of 34–41 years (adjusted odd ratio (AOR): 2.75, 95% CI (1.16–6.53)), secondary school educated mothers (AOR: 8.2, 95% CI (3.26–20.97)), daily laborer mothers (AOR: 0.22, 95% CI (0.06–0.83)), access to pipe water (AOR: 7.1, 95% CI (3.98–12.66)), access to media (AOR: 2.8, 95% CI (1.4–5.7)), and having a positive attitude (AOR: 8.6, 95% CI (2.43–31.0)) were significant predictors of maternal hygienic complementary feeding practice .Conclusions The magnitude of good maternal hygienic complementary feeding practice was low. Hence, the district health office, education office, communication office and water and energy office should work hard jointly on maternal education, pipe water supply, awareness creation and information dissemination.